LEUKOCYTE PROFILE OF BROILER SLAUGHTERED AT A CHICKEN SLAUGHTERHOUSE IN JIMBARAN BALI - Valerie Xylia Tay; Nyoman Sadra Dharmawan; I Nyoman Suartha (Buletin Veteriner Udayana, 2024)
Currently, the poultry industry is trying to meet the demand for providing nutritious meat. Therefore, broiler health is a factor that determines the success of chicken cultivation, because the good health condition of the chickens that will be slaughtered will provide a sense of security that the meat produced is healthy and suitable for consumption. The study aims to determine the total and differential broiler leukocytes, and the differences between male and female broilers slaughtered at the Chicken Slaughterhouse in Jimbaran. This study used 20 broiler blood samples obtained from 10 female and 10 male broilers. Blood samples were taken randomly before the broilers were slaughtered via the brachial vein. Total leukocytes were counted using the Auto Hematology Analyzer Rayto RT-7600 for Vet. Differential leukocyte counting is carried out by examining blood smear preparations. The examination results showed that the average total leukocytes of female broilers (83.26 x 103/µl) were not significantly different (P>0.05) from those of males (86.3 x 103/µl). Average differential of female broiler leukocytes: heterophils (23.74 x 103/µl), lymphocytes (53.01 x 103/µl), monocytes (4.11 x 103/µl), eosinophils (2.49 x 103/µl), basophils (0 x 103/µl). Average differential leukocytes of male broilers: heterophils (34.82 x 103/µl), lymphocytes (46.64 x 103/µl), monocytes (3.88 x 103/µl), eosinophils (1 x 103/µl), basophils (0.04 x 103/µl). Significant differences (P<0.05) were only found in heterophils. Morphological studies of broiler leukocytes slaughtered at the Jimbaran Chicken Slaughterhouse show that the types of leukocytes are in accordance with the reference. Further research needs to be carried out to determine the normal value and morphology of broiler leukocytes in Bali and in Indonesia in general.